Pharmacological Management of Diabetes and Its Impact on Periodontal Health: A Dentist-Pharmacist Collaboration - Ahmed Oudah Abughandar, Abdulraouf Abdulaziz M Alhejaili, Othman Nazzal Alshammari, Mamdouh eidhah saad alharthi, Dr. Awad Yahya Ali Shaher, Dr. Yasser alhassan Almashiakhy; Dr. Adel Yahya Ali Shahir, Mohammed Ahmed Arishi, Abdulrahman Mohammed Alshamrani, MOAMMAR HASSAN MOSHRIF ALAMRI, Musab Mohammed, Hassan, al-Hawsawi (Journal of International Crisis and Risk Communication Research, 2024)
Aim: To explore the impact of pharmacological diabetes management on periodontal health and highlight the importance of dentist-pharmacist collaboration in patient care. Diabetes and periodontal disease share a bidirectional relationship, where each condition exacerbates the other through systemic inflammation and impaired wound healing. Effective pharmacological management of diabetes, including the use of insulin, oral hypoglycemic agents, and newer therapies like GLP-1 receptor agonists and SGLT2 inhibitors, improves glycemic control and reduces periodontal complications. However, these therapies may also pose oral health challenges, such as xerostomia and infection risk. Collaboration between dentists and pharmacists is essential to optimize care by addressing both systemic and oral health needs, fostering better outcomes through integrated patient education and coordinated treatment plans.